The impact of the new model of day care on the mental health status and cognitive functions of patients with disabilities treated in day medical care homes in Poland, 2017-2023 - Warsz, Leszek; Jankowski, Mateusz; Andrzejczyk, Agata; Gujski, Mariusz (Frontiers in Psychiatry, 2024)
Introduction: Day Medical Care Home is a care and treatment institution providing day care services for people with disabilities (mainly older adults), implemented in Poland since 2015. This study aimed to analyze the impact of the new model of day care on the mental health status and cognitive functions of older adults with disabilities treated in Day Medical Care Homes in Poland, 2017-2023. Methods: Admission and discharge reports of 949 patients treated in Day Medical Care Homes between 2017 and 2023 were analyzed. Geriatric Depression Scale (GDS-15) and Hamilton Rating Scale for Depression (HAM-D) were used to assess mental health. Cognitive functions were assessed using Mini-Mental State Examination (MMSE).Results: The mean age was 74.3 ± 8.5 years, 76.6% were women. and 62.6% lived in rural areas. The percentage of patients with moderate or severe depression measured with a GDS-15 score decreased from 58.3% on admission to 34.6% on discharge (p<0.001). The percentage of patients with depressive disorders measured with HAM-D score decreased from 48.3% on admission to 37.2% on discharge (p<0.001). The percentage of patients with dementia or cognitive disorders measured with the MMSE score decreased from 54.3% on admission to 40.5% on discharge (p<0.001). Improvement in mental health status and cognitive functions was observed in all sociodemographic groups. Conclusions: Day Medical Care Home is an effective model of day care that improves the mental health status and cognitive functions of older adults with disabilities.